Manometria de alta resolução e impedânciophmetria do esôfago e da junção esofagogástrica na doença do refluxo gastroesofágico em indivíduos com sintomas persistentes apesar da terapia com inibidor de bomba de prótons - Silva, Débora Teles Carvalho da (2019)
The drug treatment of Gastroesophageal Reflux Disease (GERD) with a proton pump inhibitor (PPI) has been very common in the medical clinic, however some patients present persistence of symptoms despite the use of the PPI. The crural diaphragm (DC) is one of the components of the esophagogastric junction (JEG), which acts as an antirefluoride barrier. Previous studies have shown that GERD patients have lower JEG pressures compared to healthy controls. The objective of this study was to verify the dysfunction of DC in PPI refractory GERD patients, through the JEG pressure analyzes. The study was prospective, quantitative, experimental, non-randomized, open and accepted in the ethics committee of the Federal University of Ceará. The volunteers came from the University Hospital Walter Cantídio and accepted to participate in the study through the term of free and informed consent. The study period was from April 2017 to December 2018. In the Laboratory of Gastroenterology Research (LABGASTRO) the volunteers were submitted to clinical evaluation by means of the anthropometric measurements, questionnaires and functional evaluation with manovacuometric tests (PImáx), 24 hour impedance and pHmetry and high resolution manometry (MAR) with standard inspiratory measures. Participants were selected in the with persistent symptoms group (n = 15) and no persistent symptoms group (n = 15). In the comparison between the groups there was no significance regarding gender, age and body mass index. The incidence of grade A and B esophagitis was higher in both groups. The 24 hour impedance and pHmetry end PImáx results values showed no difference between the groups. n the MAR with inspiratory maneuvers, in the esophageal motility phase during the swallowing, the Frontal Frontal Velocity (FVC) was higher in the group with persistent symptoms when compared with no persistent symptoms (p = 0,009). The JEG Contractility Index (CI - JEG) obtained smaller values in the refractory group in the time - controlled breathing phase, being significant (p = 0,037). In the standardized inspiratory maneuvers of the CI-JEG, the Maximum Pressures (Pmax) were lower in the group with persistent symptoms and the Axial Displacement (DS) was higher in that group. The study showed a tendency of pressures in the esophagogastric junction to be lower in the group with persistent symptoms, which may be related to a possible dysfunction of the crural diaphragm, based on previous studies